Community Empowerment through Processing Bamboo Leaves Waste into Liquid Smoke - Lina Saptaria; Samudi; Efi Rohana (PT FORMOSA CENDEKIA GLOBAL, 2022)
This Community Service activity aims to process dry bamboo leaves into liquid smoke using pyrolysis techniques. Methods of activity in the form of counseling, training, and mentoring. Participants in the activity were 30 residents of Mejono Village. The resulting product is grade 3 liquid smoke. The effectiveness of the activity is measured using the Pre-test and Post-Test values. The results show an increase in knowledge, production skills, and marketing skills for liquid smoke products. This activity can be an inspiration, motivation, and ongoing activity for the tourism management team to process dried bamboo leaf waste into liquid smoke products that can provide added value for the Gronjongwariti water tourism manager and farmers in Mejono Village.